Extent of medicolegal burden in neurosurgery – An analysis of the National Health Service Litigation Authority Database. (3rd September 2015) - Steele, Louise; Mukherjee, Soumya; Stratton-Powell, Ashley; Anderson, Ian; Timothy, Jake
Abstract : Introduction . Neurosurgery remains amongst the highest malpractice risk specialties. We aimed to better understand the medicolegal burden in neurosurgery by analysing a large volume of claims recorded by the National Health Service Litigation Authority (NHSLA). Methods . The NHSLA database was retrospectively interrogated for all closed (i.e. with legal outcomes) claims in neurosurgery recorded between 1997 and 2011. Collected data included clinical event; subspecialty; patient injury sustained; reason for claim; legal outcome and litigation costs. Results . The total neurosurgical litigation cost associated with 617 closed claims over the time period investigated was £67.4 million. 282 claims (46%) were successful with damages awarded. The annual claim volume and damages paid increased between 2002 and 2011 by 50% and 140%, respectively, and two-thirds of these increases were attributable to spinal claims. 30% of the total litigation cost was legal fees. The leading causes of damages paid in cranial surgery were delayed diagnosis (29%) and delayed treatment (24%). In contrast, the leading causes of damages paid in spinal surgery were delayed diagnosis (32%) and surgical negligence (22%). The greatest mean damages awarded per claim were for brain damage (£617, 000), compared to only £51, 000 for fatality. Conclusion . Neurosurgical litigation in NHS hospitals has significantly increased over the last decade, predominantly due to spinal claims. A neurosurgical claim has a very high likelihood of success, and even for unsuccessful claims, associated legal fees are considerable. Causes of claims are differently distributed between cranial and spinal neurosurgery, although overall, delay to diagnosis accounted for the predominant share of claims volume and damages. There was a significant medicolegal burden associated with serious long-term injury and need for life-long care as in the case of brain damage as compared with death as an outcome. This analysis represents the largest UK study on litigation in surgery to date.